Tanzania's role in Burundi's peace process - Ameir, Said J K (My University, 2009)
ABSTRACT The Arusha Peace and Reconciliation Agreement was signed in Arusha Tanzania in August 2000. This was a result of countless efforts involving countless players; a process which took nearly six years to find a durable solution to the decades - long Burundi crisis. Tanzania government is one of these players. This study therefore focuses on the role of Tanzania in the Burundi’s Peace Process. The primary argument put forth by the study is that Tanzania played multiple roles including mediation and facilitation, hosting peace talks and Burundi refugees. The study argues that whereas moral obligation could be counted for Tanzania’s involvement, the negative impacts of the Burundi crisis to Tanzania were central to its engagement. The negative impacts were perceived by Tanzanian government authorities as a threat to its national interests, hence warranted a direct response. The study acknowledges that Tanzania’s mediation and facilitation roles were marred by two controversial issues namely; being perceived as ‘biased’ (in favour of the Hutus and hostile to the Tutsis) and also as one which favoured military solutions to the conflict as opposed to other approaches advocated by other players. These allegations are discussed to determine their authenticity and conclusions are made. The study also examines whether or not the coming of Nelson Mandela (and South Africa for that matter) did influence Tanzania’s role and the conclusion is that it did influence because competition for influence between the two countries was obvious when Mandela replaced Mwalimu Nyerere as the major facilitator. The point raised here is that whereas Tanzania wanted to preserve and continue with its influence in the sub-region, South Africa on its part wanted to use that opportunity to penetrate both politically and diplomatically on the one hand and consolidate its economic presence in the sub-region on the other hand. The study asserts that although Burundi has managed to sign the Arusha Accord, secure ceasefire agreements between the Government and the rebel movements and successfully completed the transitional period, the country still faces many challenges which it needs to overcome if it is to build a new, peaceful and united society. In this regard, the study recommends continued support and responsibility by regional states and the international community coupled with close monitoring of the situation in the country. Besides, the study recognises that Tanzania’s role will still remain influential for many years to come in the peace building process in Burundi.